Prospective study on use of antibiotic prophylaxis on operative wound infections in south Indian population - Reddy, Chakarala Obula; Reddy, Garisa Chandra Mohana (International Surgery Journal, 2018)
Background: Antibiotic prophylaxis can help to reduce surgical site infections in operative wound infections. Present work was done to study the use of antibiotic prophylaxis on operative wound infection. Methods: A total of 120 patients under went various surgeries in the department of surgery, Fathima Institute of Medical Sciences, Kadapa, Andhra Pradesh utilized for the present study. Out of 120 patients utilized 86 were males and 34 females with elective surgeries and observed from their admission to discharge from the hospital and also followed up all the patients up to fifth week of post-surgery. Surgical wound types were observed and recorded. Results: We have noted clean wound cases were 91, contaminated cases were 5 and clean contaminated were 24 noted. 11 infected cases were observed in clean wound type, 3 infected cases in clean contaminated were observed. 3 patients out of 120 patients had post-operative fever and subsided within 2 days without antibiotics. Out of 91 clean wound cases, 2 patients (2.19%) had post-operative fever, 10 patients (10.9%) developed with serous discharge and purulent discharge was developed in 1 (1.09%) case in present study. Bacteriology revealed 4 cases (4.29%) showed growth of staphylococcus aureus organism, 1 case (1.09%) with pseudomonas organism was noted. 2 cases (8.3%) developed with serous discharge and 1 case (4.16%) with purulent discharge and also growth of E. coli in 1 (4.16%) case was noted in 24 clean contaminated cases in present study. Conclusions: Use of antibiotic prophylaxis has a vital role in pre and post-operative wound infections.